Long‐term health‐related quality of life in children with lymphatic malformations treated with sclerotherapy generally matched age‐appropriate standardised population norms. (24th March 2019) - Ghaffarpour, Nader; Claesson, Gösta; Wester, Tomas; Boman, Krister K.
Abstract: Aim: We assessed the long‐term health‐related quality of life (HRQoL) of children who received sclerotherapy for lymphatic malformations. This treatment involved injecting drugs into the blood vessels to make them shrink. Methods: Our cross‐sectional study retrospectively reviewed patients who received OK‐432 sclerotherapy injections at Karolinska University Hospital, Stockholm, Sweden, from 1998 to 2013. We studied 49 patients (63% female) aged 8–18 at least five years after their first injection. HRQoL was assessed with the KIDSCREEN‐52 questionnaire and a study‐specific questionnaire addressed disease consequences and patient satisfaction. We determined associations between HRQoL and disease and treatment and the patient's sex. Results: Overall HRQoL paralleled age‐appropriate norms in the general population, but some subgroups had lower levels. Regression‐based estimates showed that larger numbers of injections were negatively associated with HRQoL in the dimensions autonomy, parent relations and home life, financial resources and school environment (p = 0.01–0.03). Malformations in the head and neck area were negative predictors across dimensions and were strongest for psychological well‐being (p = 0.009), parent relations and home life (p = 0.017) and school environment (p = 0.006). Conclusion: Despite generally positive outcomes, multiple injections and malformations in the head and neck were associated with impaired HRQoL.